2020
DOI: 10.1097/md.0000000000021205
|View full text |Cite
|
Sign up to set email alerts
|

Fatal vascular complications during transradial percutaneous coronary intervention

Abstract: Rationale: Vascular complications of transradial percutaneous coronary intervention (PCI) are rare and usually occur at the access site below the elbow. However, vessels along the tract of the wire or catheter can be injured at any point, causing various types of bleeding complications. Patient concerns: A 57-year-old man visited due to chest discomfort. Coronary angiography showed significant stenosis at the distal right coronary artery (RCA). Immediately after the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The management of mediastinal hematoma mainly includes supportive treatments, analgesic therapy, appropriate fluid infusion, blood transfusion if necessary, and keeping the airway unobstructed. 11 Mediastinal hematoma after cardiac catheterization is usually benign and has a favorable prognosis. In our study, all 10 patients received conservative management, and their conditions during the hospital stay and after discharge were all stable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The management of mediastinal hematoma mainly includes supportive treatments, analgesic therapy, appropriate fluid infusion, blood transfusion if necessary, and keeping the airway unobstructed. 11 Mediastinal hematoma after cardiac catheterization is usually benign and has a favorable prognosis. In our study, all 10 patients received conservative management, and their conditions during the hospital stay and after discharge were all stable.…”
Section: Discussionmentioning
confidence: 99%
“…The management of mediastinal hematoma mainly includes supportive treatments, analgesic therapy, appropriate fluid infusion, blood transfusion if necessary, and keeping the airway unobstructed 11 . Mediastinal hematoma after cardiac catheterization is usually benign and has a favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous coronary intervention (PCI) is an extensively used medical therapy for acute and chronic coronary artery disease (CAD)[ 1 , 2 ]. Vascular complications of transradial PCI are rare and usually occur at the access site below the elbow[ 3 - 6 ]. A study population consisting of 1984998 PCI procedures performed at 1292 participating sites demonstrated that the median rate of bleeding at the access site was 0.2%-0.5%[ 7 ].…”
Section: Introductionmentioning
confidence: 99%